1999
DOI: 10.1021/bi991275y
|View full text |Cite
|
Sign up to set email alerts
|

Partial Glycosylation at Asparagine-2181 of the Second C-Type Domain of Human Factor V Modulates Assembly of the Prothrombinase Complex

Abstract: Thrombin-activated factor Va exists as two isoforms, factor Va(1) and factor Va(2), which differ in the size of their light chains and their affinity for biological membranes. The heterogeneity of the light chain remained following incubation of factor Va with N-glycanase. However, we found that the factor V C2 domain, which contains a single potential glycosylation site at Asn-2181, was partially glycosylated when expressed in COS cells. To confirm the structural basis for factor Va(1) and factor Va(2), we mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…We also observed a peak of m/z ϭ 3091.3 corresponding to a triantennary-monosialylated corefucosylated modification at Asn 2181 . Glycosylation at this site was documented by other investigators and gives rise to the observed doublet in the FVa light chain following SDS-PAGE (33,50,51). Two other potential sites of N-linked glycosylation exist on the FVa light chain; however, peptides corresponding to these sites were not observed.…”
Section: Platelet-derived Fv/va Is Specifically Modified By the Additmentioning
confidence: 72%
“…We also observed a peak of m/z ϭ 3091.3 corresponding to a triantennary-monosialylated corefucosylated modification at Asn 2181 . Glycosylation at this site was documented by other investigators and gives rise to the observed doublet in the FVa light chain following SDS-PAGE (33,50,51). Two other potential sites of N-linked glycosylation exist on the FVa light chain; however, peptides corresponding to these sites were not observed.…”
Section: Platelet-derived Fv/va Is Specifically Modified By the Additmentioning
confidence: 72%
“…We assumed that the change in intrinsic fluorescence should be proportional to the fraction of protein bound and fitted the titration data using a model that assumed four identical and independent sites (10). We have shown that there is a 3-fold difference in the affinity of both human (12) and bovine (14) FV a1 and FV a2 for PS-containing membranes. Unlike their interactions with membranes, we conclude that bovine FV a1 and FV a2 bind to soluble C6PS with comparable affinities (11 Ϯ FIG.…”
Section: Effect Of C6ps On Prothrombin Activation By Fx a In Thementioning
confidence: 99%
“…This has been attributed to substantially different affinities for binding to membranes (13). However, our lab has reported that the two forms of both bovine and human FV a bind to membranes with only ϳ3-fold different affinities (12,14). This suggests that differences in the ability to support prothrombinase activity must reflect either different binding between factors FX a and FV a1 versus FV a2 or different intrinsic activities of the FX a ⅐FV a1 and FX a ⅐FV a2 complexes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, factor VIII requires more PS per binding site than factor V (13), and current evidence implicates different domains in membrane binding. While binding of factor V is apparently mediated by both the A3 domain (17) and the C2 domain (18) and is influenced by glycosylation within the C2 domain (19), binding of factor VIII is apparently mediated by the C2 domain (20,21) and is independent of glycosylation. Recent publication of two crystal structures for the C2 domain of factor V (22) and a single structure for the C2 domain of factor VIII (23) has provided the basis for a model membrane-binding mechanism.…”
mentioning
confidence: 99%